Characterization of disease flares and impact of mepolizumab in patients with hypereosinophilic syndrome - Pane, Fabrizio; Lefevre, Guillaume; Kwon, Namhee; Bentley, Jane H.; Yancey, Steven W.; Steinfeld, Jonathan (Frontiers in Immunology, 2022)
In patients with hypereosinophilic syndrome (HES), mepolizumab reduces the incidence of HES-related clinical signs and symptoms (flares). However, reports characterizing flare manifestations are limited. The double-blind, parallel-group 200622 trial (NCT02836496) enrolled patients ≥12 years old with HES for ≥6 months, ≥2 flares in the previous year, and screening blood eosinophil count ≥1000 cells/μL. Patients maintained ≥4 weeks stable HES therapy, before randomization (1:1) to 4-weekly subcutaneous mepolizumab (300 mg) or placebo, plus baseline HES therapy, for 32 weeks. This post hoc analysis investigated flare manifestations and duration by re-examining the Core Assessments form and narrative recorded for each flare during the study. Flare symptoms were retrospectively categorized into constitutional, dermatological, respiratory, nasal, gastrointestinal, neurologic and other. The most frequently reported flare symptoms were constitutional (94% of flares), dermatological (82% of flares) and respiratory (72% of flares); flares reported in patients receiving mepolizumab compared with placebo were generally similar in terms of the frequency of symptoms reported. Mepolizumab was associated with a shorter median (range) duration of flares (10.0 [4, 126] days) versus placebo (26.0 [1, 154] days). In patients with HES, flares were associated with symptoms linked to multiple organ systems highlighting the challenges faced for treating flares. Clinical trial registration: NCT02836496, https://clinicaltrials.gov/ct2/show/NCT02836496.